Development of Comic Life as a Learning Media for Writing News Texts - Alma Wida Siwi (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2024)
This study aims to develop the Comic Life application as a learning media to improve the ability to write news texts in grade VII students. The development process involves 8 stages modified from the Borg and Gall model. Validation tests from material experts and media experts show that the application is very feasible with a percentage of 93.75% and 96.3% respectively. Assessments by students and Indonesian language teachers also showed positive results with a percentage of 86.8%, 91.33%, and 88.75%. The results of this study indicate that the Comic Life application is effective in improving the ability to write news texts in grade VII students, so that it can improve the quality of education by using innovative and interactive technology.